INOVASI TEKNOLOGI TEPAT GUNA PADA NELAYAN TRADISIONAL BAGAN TANCAP YANG TERDAMPAK KERUSAKAN PESISIR DI KABUPATEN BANGKA TENGAH - Endang Bidayani; Agung Priyambada; Mohammad Agung Nugraha (Jurnal Abdi Insani, 2022)
Traditional fishermen are community groups affected by damage to the coastal environment due to sedimentation. This is because traditional fishermen have a low fishing range (under three miles) and simple fishing technology. catch. This community service activity aims to increase the productivity of fishing aids using portable FADs and blue LED lights. The method of this activity is active participation. The result of this activity is that portable FADs and blue LED lights can increase the productivity of fishing gear, thereby increasing the quantity and quality of catches by 20%. The existence of portable fish FADs which are homes for fish plays a very important role as fishing aids. The difference between this FAD and conventional FAD is that it requires minimal manufacturing costs, and it is very possible to change locations according to the fishing area. The conclusion from PkM is that partners have knowledge related to appropriate technology that can increase catch productivity, namely portable FADs and blue LED lights.